2022
DOI: 10.3390/bs12120490
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Disordered Eating in Competitive Cycling: A Scoping Review

Abstract: This article reports on the findings from a scoping review on eating disorders and disordered eating in competitive cycling. The review was informed by a scoping review methodological framework as well as the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for scoping reviews (PRISMA-ScR) reporting guidelines. PubMed, SPORTDiscus and Web of Science were used to identify relevant literature for review. Fourteen studies met the eligibility criteria and were included in the full revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…A large proportion of reviewed papers focus on ED symptomatology or susceptibility. This may reflect cycling's complex socioenvironmental risk factors, where ED and unhealthy weight-management behaviours can be prevalent [46]. Several papers indicated that weight-related stressors are a commonly acknowledged vocational pressure (e. g. [31,33]).…”
Section: Eating Disordersmentioning
confidence: 99%
“…A large proportion of reviewed papers focus on ED symptomatology or susceptibility. This may reflect cycling's complex socioenvironmental risk factors, where ED and unhealthy weight-management behaviours can be prevalent [46]. Several papers indicated that weight-related stressors are a commonly acknowledged vocational pressure (e. g. [31,33]).…”
Section: Eating Disordersmentioning
confidence: 99%
“…Signi cantly, such practices could render athletes vulnerable to comorbid physical and mental health conditions; alongside associations with clinical and subclinical ED presentations [39], adverse weight-management behaviours have been linked to low energy availability and increased risks for RED-S [9,40], heart disease [8], obsessive compulsive disorder [41] substance use disorders [42], and exercise addiction [10]. Furthermore, there have been reports of support teams, medical staff, and other stakeholders closely monitoring racers' anthropometrics, body mass composition, and optimal weight, which has ampli ed weight-related pressures and injurious habits [9,18,43].…”
Section: Implications For Athlete Wellbeingmentioning
confidence: 99%
“…Owing to the performance-based associations of low weight and environmental and social in uences, clinical and subclinical EDs and harmful weightmanagement behaviours may be prevalent within cycling [10]. Evidence indicates that elite-level riders can often adopt an extreme approach to weight loss, including disordered eating [11,17], fasting [13], self-induced vomiting [9], the use of laxatives [13], and weight cycling in the lead up to competitions [38].…”
Section: Implications For Athlete Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations